Grey Gardens [videorecording (DVD)] - Maysles, Albert; Maysles, David; Beale, Edith Bouvier, -1977; Beale, Edie, 1917-2002; Torre, Gerard Joseph; Wright, Lois (Criterion collection, 2006)
Grey Gardens spawned everything from a midnight-movie cult following to a Broadway musical to an upcoming Hollywood adaptation. Later the filmmakers went back to their vaults to create this tribute to both the Beale women and their legion of fans. This edition includes the original 1975 documentary. Companion title, part two, Beales of Grey Gardens, was created in 2006 and includes archival footage.